Revitalisasi Pendidikan Agama Islam dalam Membangun Karakter Siswa, Studi kasus di MTs Baitul Arqom - Moya Sabhana; Opik Taufikurrahman; Dadan Rusmana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
As a nation with a predominantly Muslim population, Indonesia bears a profound responsibility to cultivate Islamic religious education (PAI) that transcends mere knowledge transfer and serves as a means to shape the character of the younger generation. PAI is anticipated to foster a character rooted in the noble values of Islam, as well as to internalize moral and ethical principles as guiding standards in daily life. However, religious education at the school level faces considerable challenges, as conventional teaching methods tend to result in minimal student engagement. This research aims to explore the impact of revitalizing Islamic religious education at Madrasah Tsanawiyah Baitul Arqom on the character development of students. Employing a qualitative approach, this study utilizes interviews, participatory observations, and focused group discussions to gather data. The analysis reveals that the implementation of routine activities, such as dhuha prayers, exemplary teaching by educators, and active learning methods positively contributes to the enhancement of students' discipline, sense of responsibility, and social concern. This research also uncovers a positive correlation between the quality of religious education and the character development of students, thereby underscoring the necessity for innovation within the curriculum and teaching methodologies of PAI. Recommendations are put forth for the development of educational programs that are more responsive to the demands of the times and the aspirations of the younger generation, ensuring that religious education in Indonesia can cultivate individuals who are intellectually astute and morally upright.